Comparison of fuzzy and PID based governor's response in utilization of DG spinning reserve - Laghari, J.A.; Mokhlis, Hazlie; Bakar, Ab Halim Abu; Karimi, M.; Mohammad, H. (Society of Polish Electrical and Electronics Engineers, 2013)
When tripping events or overloading cases occur in power system, load shedding scheme operates to shed some load and stabilize the frequency. However, amount of load to be shed greatly depends on, how fast governor can utilize DG spinning reserve. This paper compares the response of DG with fuzzy based governor and PID based governor in utilization of DG spinning reserve. The simulation results show that DG with fuzzy based governor utilizes spinning reserve more quickly and requires lesser load to be shed than a DG with PID based governor.